Bäcklund transformations and nonlinear differential difference equations - Levi, D. (1980)
It is shown that any Bäcklund transformation of a nonlinear differential equation integrable by the multichannel Schrödinger eigenvalue problem can be written in the form V(x) = U′V - VU. This allows us to interpret the Bäcklund transformation formally as a nonlinear differential difference equation for which we can immediately construct the soliton solutions.